Process Documentation: Operationalizing ICT Women's Center for Skills Training for Employment - Radhika Iyengar; Haein Shin; Joaquin Aviles Lopez; Srinivas Akula (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2019)
The process of initiating and operationalizing a concept-combining multiple Sustainable Development Goals (SDGs) to improve educational and employment opportunities for women-is outlined in this document. The result of this endeavor is a fully functioning ICT Women's Center in Telangana State, India, powered by solar energy, where skills trainings offered in the areas of computer, English, life skills and environment, aim to prepare young women for future careers and job opportunities. The document outlines various components that were required to begin operationalizing the Center, from infrastructural inputs to curriculum design and delivery. Initial months of operation revealed the high demand for the skills training provided through the Center, and as a result, continuous updates to the Center operations and programs are explored to accommodate the needs of newly interest participants as well as to continuously build upon initial training. The initial months also shed light on the importance of: active involvement of local leadership at each stage of project development; engagement of local district government leadership and offices (rural development office, public health initiatives); establishment of relationship with local educational institutions; and collaboration and enthusiasm of all parties involved in setting up the Center. The components outlined in the document will continue to develop as the operations moves forward. Particularly, continued efforts will take the forms of: monitoring energy production and consumption at the Center; partnerships strengthened with local educational institutions as well as target populations for computer skills training; engagement with local employers and input from local professionals as mentors and speakers on curriculum contents; building additional support for participants through advancing curriculum contents and related activities, based on participant feedback and course evaluations.
Keywords: 330